2018
DOI: 10.1186/s40497-018-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Mann Whitney Wilcoxon test in the survival analysis of newly established companies in Tunisia (Case of the sfax region)

Abstract: This research focuses on the factors of survival and growth of new enterprises in Tunisia. Based on previous research, we hypothesize that three factors influence the survival and growth of these firms: factors related to the entrepreneur, factors related to organizational characteristics and characteristics of the environment from start-up. We test these assumptions on a sample of 60 companies. The results show that human capital and the experience of the entrepreneur have a relatively small impact on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The process was followed in two rounds at both universities until the samples with the appropriate characteristics and size were completed. Performed the Mann-Whitney test, it was found that only two of the fourteen variables observed had asymptotic bilateral significance greater than 0.05, which is why it is confirmed that the two samples are independent [162]. Initially, the total sample included 47 more subjects who were eliminated because they responded with the same score to all the items or because they left some item unanswered, which indicates that the answer was 93.48%.…”
Section: Sample and Data Collectionmentioning
confidence: 94%
“…The process was followed in two rounds at both universities until the samples with the appropriate characteristics and size were completed. Performed the Mann-Whitney test, it was found that only two of the fourteen variables observed had asymptotic bilateral significance greater than 0.05, which is why it is confirmed that the two samples are independent [162]. Initially, the total sample included 47 more subjects who were eliminated because they responded with the same score to all the items or because they left some item unanswered, which indicates that the answer was 93.48%.…”
Section: Sample and Data Collectionmentioning
confidence: 94%
“…The study started by exploring the differences in the perceptions of each gender toward formal and informal institutions using the Mann–Whitney U test. This test was chosen because it is suitable for nonparametric variables, such as those considered in the present study (Harris and Hardin, 2013; Ayadi and Ghorbel, 2018). Given that our dependent variable is a dummy variable (namely, the likelihood that an individual will become an entrepreneur), we used a binomial logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…If the user still purchases power at the sales company c j after the observation period, this case is defined as right censoring [13]; the setting variable M indicates whether the user data is censored data during the analysis, and M = 1 indicates the data that is censored data. If the data is censored, the survival probability must be calculated in a time-phase.…”
Section: Calculation Methods Of Power User Churn Ratementioning
confidence: 99%